Interactive E-Module Based on Transformative Multicultural Education to Enhance Elementary Students’ Self-Determination - Ni Luh Gede Diantari; I Wayan Widiana; Komang Alit Wahyuni (Journal of Education Technology, 2026)
Low self-determination among elementary school students remains a critical issue because learning practices often rely on printed textbooks, teacher-centered instruction, and limited integration of digital media. This study aimed to develop and evaluate an interactive e-module using a transformative multicultural education approach to enhance elementary school students’ self-determination. The study employed a research and development design using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The effectiveness test used a pretest-posttest control group design involving 64 fourth-grade students, consisting of 32 students in the experimental group and 32 students in the control group. Data were collected through expert validation sheets, teacher and student response questionnaires, and a self-determination questionnaire. Data were analyzed using percentage analysis, normality and homogeneity tests, equivalence testing, and an independent sample t-test. The results showed that the e-module was highly valid based on expert validation, highly practical based on teacher and student responses, and effective in improving students’ self-determination. The hypothesis test showed a significant difference between the experimental and control groups. These findings indicate that interactive e-modules integrating transformative multicultural values can strengthen autonomy, competence, and relatedness in elementary learning.